Ahmet Davutoglu's foreign policy concept of "Strategic depth" and the kurdish issue - E. I. D. Mehmet; A. K. Magomedov (Современная наука и инновации)
The article is devoted to the content and basic principles of the foreign policy concept set out in the book "Strategic Depth" by former Turkish Foreign Minister and Prime Minister Ahmet Davutoglu. The article examines the historical prerequisites for the formation of a new foreign policy concept of Turkey in the 21st century, the main ideas and principles formulated by A. Davutoglu in his work. It is pointed out how the political reality of recent decades has seriously adjusted many provisions of the doctrine of "strategic depth", but despite this, its basic principles and approach are still relevant for Turkish diplomacy. The correlation between the provisions of the "Davutoglu doctrine" and the Kurdish problem in Turkey, which has both domestic and foreign policy significance for this country, is analyzed. Davutoglu's view that a peaceful settlement of the Kurdish issue was urgent for Turkey's strategic interests was innovative and politically far-sighted. The result of the implementation of this doctrine was that in the first decade of the 21st century, not only relations with Kurdish leaders changed positively, but also relations with neighboring countries, which were largely determined by the "Kurdish issue".